PENGARUH MANAJEMEN WAKTU, STRES AKADEMIK, DAN MOTIVASI BERPRESTASI TERHADAP KEAKTIFAN DI DALAM KELAS MAHASISWA PENDIDIKAN EKONOMI UNIVERSITAS JAMBI ANGKATAN 2023 - Azhi Ridho Al qowi; Muhammad Arif Liputo; Sahara (STKIP Subang, 2026)
This study was motivated by the persistently low level of engagement among some students during classroom learning, evidenced by a lack of participation in asking questions, engaging in discussions, expressing opinions, and participating in learning activities. This situation is believed to be influenced by internal factors such as time management, academic stress, and achievement motivation. The study aims to determine the impact of time management, academic stress, and achievement motivation on the classroom engagement of Economic Education students (Class of 2023) at the University of Jambi. A quantitative approach utilizing the ex-post facto method was employed. The study population consisted of 112 students, with a sample of 88 students determined using Slovin's formula and proportionate random sampling. Data were collected via a Likert-scale questionnaire and analyzed using descriptive analysis, prerequisite analysis tests, multiple linear regression, t-tests, F-tests, and the coefficient of determination (R²) test. The results indicate that time management, academic stress, and achievement motivation each have a significant effect on classroom engagement. Simultaneously, these three variables also significantly influence student engagement. Therefore, improving time management skills, managing academic stress, and strengthening achievement motivation are necessary to enhance student engagement in the learning process.